Aflatoxina M1 e bifenilos policlorados (PCBs) em leites produzidos em sistemas convencional e orgânico - Pigatto, Giane Magrini (2018)
Aflatoxin M1 and polychlorinated biphenyls (PCBs) are toxic compounds and carcinogenic to humans. Both have their widespread occurrence through milk in a significant way. Milk is an important source of human exposure to these compounds also due to its expressive consumption worldwide, either in the fluid form or dairy prodtucs, mainly by young and elderly. Organic milk is geting space and preference for many consumers, since its production is standardized and can be certified according to animal welfare, sustainability, non-use of antibiotics, synthetic medicines and homones, for example, with a view to obtaining products without residues. In this study, 84 milk samples were investigated in total, and 63 (75 %) were contaminated with aflatoxin M1 above the limit of detection. No difference was observed between the samples from organic and conventional systems. There was no difference between pasteurized and raw milk samples. None of the samples contained aflatoxin M1 above the maximum level permitted by Brazilian Legislation (0,5 μg/kg for fluid milk). The levels of eleven congeners of polychlorinated biphenyls (PCBs) were evaluated in 60 samples of organic and conventional milk collected in three regions of Brazil. The congeners of four DL-PCBs investigated were not detected in any sample of milk analyzed. The results confirm the occurrence of low contamination by PCBs 153 and 180 in the two production systems, with a significant difference in the mean concentration detected for PCB 153 in conventional milks PCB 153 was present in average concentrations of 0.46 ng g-1 fat in organic milks and 1.12 ng g-1 fat in the conventional samples analyzed. PCB 180 was detected at mean concentrations of 0.12 ng g-1 fat and 0.18 ng g-1 fat in organic and conventional samples, respectively. These detected levels were in line with European legislation (40 ng g-1 for sum of indicator PCBs). PCB 153 was present in average concentrations of 0.46 ng g-1 fat in organic milks and 1.12 ng g-1 fat in the conventional samples investigated. There was no significant difference between the occurrence of PCB 153 and PCB 180 in raw and pasteurized milks. PCB 153 was detected in 50% of the conventional milk samples and in 13.33% of the organic samples analyzed. PCB 180 was detected in 10% of the conventional samples and in 6.66% of the organic milk samples analyzed.The levels detected were in accordance with the european legislation. The estimated daily intake (EDI) of aflatoxin M1 e PCBs through organic and conventional milk consumption was also evaluated. In this study, the EDI-values for aflatoxin M, PCB 153 e PCB 180 did not pose a toxicological risk for the population. However, it is suggested to consider the data obtained, especially in milks from organic production, as an impact factor on organic quality. In this sense, the systematic monitoring can be as a subsidy to the evaluation of the risk involved in the consumption of milk against the contamination by AM1 and POPs of hight toxicity, such as PCBs. To our best knowledge, this is the first report on aflatoxin M1 and PCBs levels in organic milk from Brazil.